A Review of Self-Compassion & Psychological Well-Being among Counselors in Malaysia - Voon, Siok Ping; Lau, Poh Li; Leong, Kwan Eu (Global Academic Excellence, 2017)
Counseling has been recognized as both challenging and rewarding. Malaysia, as a developing country has placed more emphasis on the mental health of the population. Thus, one could foresee the growing demand for counselors in Malaysia and their professionalism in the future seeing that counselors appear to be one of the professionals needed in helping people with many different mental health conditions. Counselor psychological well-being is important to the therapeutic relationship, process and treatment effectiveness. Thus, having a sense of psychological well-being is crucial for professional competency. Self-compassion has emerged as a healthy and positive attitude in enhancing counselors’ psychological well-being. However, these essential concepts have not been given much attention in Malaysia. Therefore, this paper reviews the concepts of psychological well-being and self-compassion, especially their relevance to counselors. Also, this paper highlights the significance of future research on selfcompassion and psychological well-being among counselors in Malaysia.